Contact dermatitis in the construction industry: the role of filaggrin loss‐of‐function mutations3. (12th December 2015) - Timmerman, J.G.; Heederik, D.; Spee, T.; van Rooy, F.G.; Krop, E.J.M.; Koppelman, G.H.; Rustemeyer, T.; Smit, L.A.M.
Summary: Background: A high prevalence of contact dermatitis (CD) and respiratory symptoms has been observed in the construction industry, probably due to widespread exposure to irritants and allergens. It is unknown whether carriers of loss‐of‐function mutations in the gene encoding filaggrin ( FLG ), a known risk gene for eczema and asthma, are at increased risk. Objectives: To investigate associations of FLG mutations with CD and respiratory symptoms in Dutch construction workers. Methods: A questionnaire including items on dermal and respiratory symptoms such as wheeze, shortness of breath and asthma was administered to construction workers. Total and specific serum IgE was analysed by enzyme immunoassays. Four FLG loss‐of‐function mutations were genotyped. CD was diagnosed by a team of a dermatologist and a clinical occupational medicine specialist using photographs of the subjects' hands and self‐reported questionnaire data. Results: Of the 506 participating workers, 6·3% carried at least one FLG mutation. Mild CD was diagnosed by the specialists in 34·0%, and severe CD in an additional 24·3%. CD was considered work related in 282 of 295 subjects (95·6%). Carriers of FLG variants had an increased risk of CD compared with subjects carrying wild‐type alleles [mild CD: odds ratio (OR) 5·71, 95% confidence interval (CI) 1·63–20·06; severe CD: OR 8·26, 95% CI 2·32–29·39]. FLG variants and the presence of CD were not associated with respiratory symptoms and atopy. Conclusions: Contact dermatitis prevalence in construction workers is high. FLG loss‐of‐function mutations increase the risk of CD even further. FLG mutations were not associated with respiratory symptoms or atopy. Abstract : What's already known about this topic? The prevalence of self‐reported skin symptoms and contact dermatitis is high in construction workers. Filaggrin loss‐of‐function mutations have been related to atopic dermatitis and respiratory symptoms. What does this study add? Dermatological evaluations confirm a high prevalence of occupational contact dermatitis in construction workers. Filaggrin loss‐of‐function mutations were strongly related to contact dermatitis in construction workers. Filaggrin loss‐of‐function mutations were not associated with respiratory symptoms or atopy in construction workers. Linked Comment: Brown, Br J Dermatol 2016; 174: 263–265 . Plain language summary available online